The Impact of Unimplemented Large-Scale Land Development Deals - Broegaard, Rikke Brandt; Vongvisouk, Thoumthone; Mertz, Ole (Frontiers in Sustainable Food Systems, 2022)
Although many land deals are never implemented to production stage, little is known about how abandoned projects affect local communities and the government agencies that promote them. This article analyses the effects on local actors, their land access, land use and tenure security of a large-scale bio-fuel land deal in northern Laos that a Chinese company initiated but subsequently abandoned before reaching the planting and production stage. The project left local people bound by contracts without cancellation clauses and with livelihood losses, until the investment contract eventually was annulled by Lao state actors. The deal has prepared the provincial government to receive new investors to further the modernization of agriculture and a land-based economic growth, both in terms of identifying land for development, and experiences gained of how to handle international investors. However, it seems unlikely that local actors can decline future projects when interests of investors and government actors overlap–interests that may not be limited to those officially stated as the objectives of the land deal. A more accurate terminology and additional research is needed to shed light on the outcomes of land deals that for some reason never reach a production stage, whether as a “virtual,” or “failed” land deal.